Peningkatan Kemampuan Literasi Numerasi pada Anak Kelompok A melalui Permainan Manipulatif di KB Anugerah Sebayan - Nurliza; Yeti; Nurriza (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study aimed to improve the numeracy literacy skills of Group A children through the implementation of manipulative games. The study employed a qualitative approach using Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The numeracy literacy indicators examined included the ability to count objects from 1–10, recognize number symbols from 1–10, and understand the concepts of more and less. The results showed a gradual improvement in children’s numeracy literacy skills. In the pre-cycle stage, the average percentage was 43.52%, categorized as Not Yet Developed (NYD). In Cycle I, through the Sentar Angka game, it increased to 59.26%, categorized as Beginning to Develop (BD). In Cycle II, through the Ambil Hitung Kacang Tanah game, it further increased to 70.37%, reaching the Developing as Expected (DE) category. These findings indicate that manipulative games are effective in improving early childhood numeracy literacy skills.